Design and Analysis of Optimum Performance Pacemaker Telemetry Antenna - N. H. Sulaiman; N. A. Samsuri; M. K. A. Rahim; F. C. Seman; M. Inam (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The demand for health technology is increasing especially in the telemetry applications. These applications generally use implanted antennas to be utilized for data transfer from patients to other reader devices. This procedure can make the health care more efficient since it provides fast diagnosis and treatment to the patient. Therefore, in order to effectively implement an implanted antenna inside the human body, thorough numerical analysis and simulations are required prior to the fabrication of antenna. In this work, an implanted antenna has been proposed to be designed at 402.5MHz within the biomedical frequency band of 402- 405MHz. By introducing a compact loop antenna for telemetry applications in a Pacemaker, a number of advantages can be achieved for health care such as efficient data information and quick diagnosis. Moreover, in this work an investigation of compact loop antenna with casing in Pacemaker has been carried out by placing the antenna inside the phantom of human body model.